News and noise in crime politics: the role of announcements and risk attitudes - Wolfgang Maennig; Stefan Wilhelm (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2022)
We examine the short- and medium-term effects of announcements of changes in anti-crime policies in the distant future (news shocks) and provide a first extension of the analysis to cases where the announced policy changes may not be realized in the end (noise shocks). We further innovate by analyzing the effects of policy changes that increase the variance while holding the expected values of policy instruments constant. We confirm that news shocks can bring about immediate changes in delinquency. However, announcements of tighter anti-crime policies may even increase delinquent activities, at least temporarily. In the case of noise shocks, we observe persistent reactions of potential offenders, indicating that a credible communication strategy may generate an impact on crime politics. Finally, increasing the variance of policy instruments without changing the mean expected detection rate may have similar effects.
Keywords: 330; Kriminalpolitik; Ankündigungseffekt; Schock; Straftäter; Risikopräferenz; Kriminalität; Kriminalitätsökonomik; Theorie